3v+6=5v

Simple and best practice solution for 3v+6=5v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3v+6=5v equation:


Simplifying
3v + 6 = 5v

Reorder the terms:
6 + 3v = 5v

Solving
6 + 3v = 5v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-5v' to each side of the equation.
6 + 3v + -5v = 5v + -5v

Combine like terms: 3v + -5v = -2v
6 + -2v = 5v + -5v

Combine like terms: 5v + -5v = 0
6 + -2v = 0

Add '-6' to each side of the equation.
6 + -6 + -2v = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -2v = 0 + -6
-2v = 0 + -6

Combine like terms: 0 + -6 = -6
-2v = -6

Divide each side by '-2'.
v = 3

Simplifying
v = 3

See similar equations:

| -29+11r+9n-2r-3n-11= | | 17s=-18+14s | | 12x-2=20x+4 | | 2+7cos(x)=4sin^2(x) | | M^2+6m+11=6 | | 12-4b=-8 | | 2w+2(3w+8)=28 | | 2=72/x | | y=x^3-9*x^2+24*x-18 | | 7p-9=-1+8p | | y-7/3=2 | | -6n+10=4-8n | | 10c=2+8c | | 3(b+3)+4(b+2)+b=89 | | 11=-3+z | | 24x+4=19x+4 | | 3x-(4x+6)=x-9 | | 11=-4.9t^2+120t | | 10x^2+12x-1=4x | | 8-(5/7)x-32 | | 2w+3(w+2)+2(w+5)=44 | | -10+k=10-9k | | -9j+10=10j | | -4a+16+6a=-9a | | (7x+3)(x-5)=-2x(5x+6)+x-19 | | -6-7f=-6f | | X-27=84 | | t-10=10-9t | | 2+7cosx=4sin^2x | | 12x+14=134 | | y+2(y+3)+3(y+1)=45 | | 4p-7.3=16.7 |

Equations solver categories